Precarity and Its Metaphors: Falla humana by Diamela Eltit - Cabrera, Federico (2026)
This article aims to analyze the novel Falla humana (2023) by Diamela Eltit by examining the rhetorical configurations of the notion of precarity. To this end, the study adopts a theoretical and methodological perspective that treats literature as a distinct form of social discourse. Through this lens, the article argues—as a central hypothesis—that the category of precarity functions within the novel as an ideologeme. Precarity structures the narrative not only in its representation of a social and political landscape decimated by the encroachment of neoliberal logic on life but also through the deployment of metaphors exploring the subversive potential of literary practices in contexts of vulnerability. Accordingly, the analysis focuses on three key topics: the spatial and temporal construction of the narrative, the building of barricades as a strategy of resistance, and the labor of the narrators.